Direct in vivo evidence of activated macrophages in human osteoarthritis. Issue 9 (September 2016) - Kraus, V.B.; McDaniel, G.; Huebner, J.L.; Stabler, T.V.; Pieper, C.F.; Shipes, S.W.; Petry, N.A.; Low, P.S.; Shen, J.; McNearney, T.A.; Mitchell, P.
Summary: Objective: Through binding to folate receptor-β (FR-β), the new 99m Tc–EC20 (Etarfolatide) imaging technique detects activated but not resting macrophages in vivo . The goal of this study was to investigate macrophage-related inflammation in osteoarthritis (OA). Methods: Twenty-five individuals (50 knees) with symptomatic OA of at least one knee underwent SPECT-CT imaging of both knees and planar imaging of the whole body after injection of Etarfolatide. Scans and knee radiographs were scored blinded to clinical information including knee and other joint site pain severity. Measures of association controlled for age, gender, body mass index (BMI) and employed repeated measures to adjust for correlation between knees. Design: Activated macrophages were present in the majority (76%) of knees. The quantity of knee-related macrophages was significantly associated with knee pain severity ( R  = 0.60, P  < 0.0001) and radiographic knee OA severity including joint space narrowing ( R  = 0.68, P  = 0.007), and osteophyte ( R  = 0.66, P  = 0.001). Macrophages were also localized to joints commonly affected by OA including hand finger joints (12%), thumb bases (28%), shoulders (26%), great toes (18%) and ankles (12%). The presence of joint pain at fingers, wrists, ankles and great toes was significantly positively associated with presence of activated macrophages at these sites ( P  < 0.0001–0.04). Conclusions: This study provides the first direct in vivo evidence for macrophage involvement in OA in a substantial proportion of human knees. The association of quantity of activated macrophages with radiographic knee OA severity and joint symptoms suggests that drugs targeting macrophages and macrophage-associated inflammatory pathways may have the potential to be both symptom and structure modifying.